The ability of Sitophilus oryzae (Coleoptera, Curculionidae) to transmit Mycobacterium bovis: Morphology, cultural biochemical properties of the bacteria - V. V. Zazharskyi; K. V. Alifonova; V. V. Brygadyrenko; N. M. Zazharska; V. P. Goncharenko; V. V. Solomon (Regulatory Mechanisms in Biosystems, 2023)
The problem of tuberculosis has been relevant for many years due to active spread of the infection pathogen around the globe, in particular in Ukraine. In this article, we determined the epizootic role of the rice weevil (Sitophilus oryzae (Linnaeus, 1763); Coleoptera, Curculionidae) in the spread of Mycobacterium bovis. We identified the effect of the beetle on properties of the pathogen, particularly the changes in morphology, cultural, biochemical, and biological properties after the bacteria had travelled through the body of the rice weevil. To achieve our objectives, we used the museum 100th passage of the virulent strain of M. bovis. We employed microscopic, cultural, biochemical, biological (infecting the biological model), pathoanatomic, histological methods, and PCR studies. The rice weevil is able to retain mycobacteria and release them into their environment for 30 days after becoming infected, with gradual decrease in the number of microbial cells. According to morphology and cultural properties, the pathogen we isolated in the experiment was identical to the initial culture. Enzymatic activity of the bacteria varied. The bacteria that had passed through the intestines of M. bovis were observed to have changes in the biochemical parameters which helped them to adapt to the new environment. We measured the effect of the rice weevil on pathogenicity of M. bovis, isolated directly from the beetle and from grain contaminated with the insects during the experiment. The practical importance of the study consists in expansion of our understanding of the ways M. bovis spreads, identification of effect the rice weevil has on mycobacteria. It also might help in the search for ways to interrupt the chain of tuberculosis transmission – prevention of spread of the disease to favourable areas.